Mobile Assisted Language Learning Through Cake App: Enhancing Students’ Reading Comprehension at SMPN 1 Pucuk - Salsabilla Nurfitriana Fatikha; Daniar Sofeny; Syifa’ Khuriyatuz Zahro; Buyun Khulel (Lembaga Teewan Journal Solutions, 2026)
This study analyzed the efficiency of Mobile-Assisted Language Learning (MALL) using the application named Cake in improving the students’ reading comprehension skills at SMPN 1 Pucuk. A quantitative method using a pre-experimental design of one group pretest-posttest was used. Thirty eighth graders having problems with their reading comprehension participated in this study. The data collected was obtained through administering reading comprehension tests to the students both before and after the administration of treatment. The data collected was then analyzed using descriptive statistics, Shapiro-Wilk normality test, and paired sample t-test through the use of the Jamovi software. From the descriptive statistics, there was a remarkable improvement in the performance of the students in terms of reading with their average scores increasing from 46.1 to 86.4. There was also evidence of normal distribution of data (W=0.974, p=0.654). Moreover, the output obtained from conducting paired sample t-test on the scores obtained before the treatment and after the treatment was significantly different (t(29) = -23.5; p < .001). The finding indicates that the impact of the treatment in enhancing the reading skills of the subjects was significantly significant. Based on the findings, the Cake App can be considered as a MALA for enhancing the reading skills among junior high school students